Targeting the androgenic pathway in elderly patients with castration-resistant prostate cancer: A meta-analysis of randomized trials. Issue 43 (October 2016) - Roviello, Giandomenico; Cappelletti, Maria Rosa; Zanotti, Laura; Gobbi, Angela; Senti, Chiara; Bottini, Alberto; Ravelli, Andrea; Bonetta, Alberto; Paganini, Giovanni; Generali, Daniele
Abstract: Background: The novel hormonal drugs have recently entered in the armamentarium of therapies for treatment of metastatic castration-resistant prostate cancer (CRPC). First reports are available for their use in elderly men with CRPC. Method: A meta-analysis of randomized controlled trials (RCTs) has been performed. PubMed, the Cochrane Library, and American Society of Clinical Oncology (ASCO) University Meeting were searched for data on the use of new hormonal treatment in elderly patients with CRPC. Results: Nine studies for a total of 3512 elderly patients were available for meta-analysis. Six studies reported outcomes of patients aged >75 years old while 2 studies reported on patients aged >70 years old. The pooled analysis of the androgen synthesis inhibitors revealed significantly increased overall survival (OS) due to antiandrogen agents compared with placebo or placebo and prednisone (hazard ratio (HR) for death: HR = 0.74, 95% CI: 0.67–0.82; P < 0.00001). Moreover, the new antiandrogenic therapy significantly improved the progression-free survival (HR = 0.45, 95% CI: 0.31–0.65; P < 0.0001). The incidence of any grade ≥3 adverse effect was only moderately higher during with the antiandrogenic therapy as compared to the control arms (response rate = 1.03, 95% CI: 0.88–1.20; P = 0.72). Conclusion: This study confirmed that agents targeting the androgen axis (i.e., enzalutamide, abiraterone) significantly prolonged OS in elderly men with CRPC. Abstract : Supplemental Digital Content is available in the text